The response of gut-associated lymphoid tissues (galt) following intranasal administration of Pasteurella multocida type B2 in rats - Nor Satinati Suffian @ Choy Kwai.
A total of 12 adults, Spraque-dawley rats, supplied by the animal breeding unit, Faculty of Veterinary Medicine, UPM, were used in this study. The rats were divided into 2 groups, which consist of 6 rats per group. 0.5ml of 10 CFU of P. multocida B2 was given to the rats in first group through intranasal route by using 1 ml syringe while the second group was given 0.5ml normal saline using the same method. Both groups were kept in cages separately for 2 weeks before being euthanased. The number and size of Peyer's patches of the intestine were counted and measured macroscopically upon euthanasation. The intestine was then divided into 14 portions; proximal, middle and distal of each the duodenum, jejunum, ileum and colon, and one each for caecum and rectum for histological evaluation. The Hematoxylin and Eosin staining was used to count the number of lymphocytes follicles and intraepithelial lymphocytes. This stain also used to measure the size of lymphoid follicles. The Methyl Green Pyronin was used to count the number of plasma cell. The results showed that intranasal administration of Pasteurella multocoda B2 has slight influence on the development of GALT. However, the different in the parameters study between control and infected groups were not significant (P>0.05).